Macro- and micro-morphological characteristics of Kickxia Dumort. and some related taxa in Saudi Arabia (Bangladesh Journal of Plant Taxonomy, 2022)
The morphological and anatomical aspects of 13 species belonging to genera Kickxia, Scrophularia, and Plantago of Saudi Arabia reveal that the species of Kickxia and Scrophularia are distinct from Plantago major. The most notable morphological differences are the absence of adventitious roots and the presence of acaulescent stem in the species of Kickxia and Scrophularia and the existence of adventitious roots and the absence of acaulescent stem in P. major. The species of Plantago possessed rose-shaped radical leaves, whereas the rest of the species studied had cauline leaves or both. The species of Kickxia and Scrophularia have pentamerous flowers with bilabiate corollas, whereas, P. major has tetramerous flowers with tubular corollas. The separation of P. major from the rest of the studied species is the most obvious result obtained from the dendrogram, and this result is consistent with some traditional taxonomic studies that placed Kickxia in the Scrophulariaceae species while separating P. major into an independent family Plantaginaceae. The anatomical findings revealed that the upper and lower epidermal cells of the leaves were irregular with undulate walls in all analyzed species, except in P. major, where they were polygonal with straight walls. Only P. major had amphianisocytic paracytic stomata, but eight Kickxia species had anomocytic stomata and K. hastata and K. abhaica, and the two Scrophularia species had anisocytic stomata. Therefore, this study suggests the retention of the Kickxia in Scrophulariaceae s.l. and maintaining Plantago in Plantaginaceae s.s.Bangladesh J. Plant Taxon. 29(1): 1-11, 2022 (June)